Effects of Roselle (Hibiscus sabdariffa L.) Calyx Extract Improves the Physicochemical Characteristics, Antioxidant Activity and Consumer Preference of Yogurt Dressing: Effect of roselle on yogurt dressing - Shin, So Yeon; Oh, Hyeonbin; Joung, Ki Youeng; Kim, Si Yeon; Kim, Young Soon (Progress in Nutrition, 2021)
Roselle (Hibiscus sabdariffa L.) calyx is rich in anthocyanins, organic acids, and other phenolic compounds. In the present study, Roselle calyx extracts at varying concentrations were used as supplement in yogurt dressing, and physiochemical characteristics, antioxidant activity, and consumer preference were investigated. Control yogurt dressing was made with lemon juice, and four samples were prepared with different concentrations of Roselle calyx extracts (5 g/100 mL, 10 g/100 mL, 15 g/100 mL, and 20 g/100 mL). As the concentration of the Roselle calyx extract supplement increased, the pH of the dressing decreased. Higher concentration of Roselle calyx extract supplement resulted in increased total soluble solids content, viscosity, redness, and total polyphenol and flavonoid content of the dressing. ABTS and DPPH radical scavenging activity increased with increasing concentration of the added extract. Consumer preference test rated dressings made with 15 g/100 mL and 20 g/100 mL of Roselle calyx extracts with higher scores than control. Our results suggest 15 g/100 mL ~ 20 g/100 mL of Roselle calyx extract as the optimal concentration for preparation of yogurt dressing. Roselle calyx as a natural pigment and antioxidant is a useful ingredient in food industry.